Detección de arbovirus en mosquitos Aedes aegypti en dos comunidades de Manabí, Ecuador - Wilca Cepeda, Álvaro Steeven (2024)
The arboviruses transmitted by Aedes aegypti cause a substantial problem in Ecuador, since they can be persistent, emerging, and re-emerging. During the SARS COV-19 pandemic, these diseases took a backseat. As the arboviruses are transmitted by Aedes argypti, the present study sought the molecular characterization of the different species of arboviruses within this species of mosquito collected in two communities, Caja Fuego and San Gregorio, in the province of Manabí. For this, i) a total of 468 mosquitoes were collected, 385 mosquitoes in the rural community of Caja Fuego and 83 in the marginal urban area of San Gregorio. ii) The samples were transported with all permits and biosafety regulations to CISeAL. iii) The samples were homogenized following the TRI Reagent® protocol. iv) Three methodologies were applied (end 56 point PCR, RT-PCR and Sanger sequencing), and vi) different arboviruses were identified. Regarding the results, flavivirus and alphavirus were identified. For flavivirus, of a total of 22 samples, 18 were positive, and of these, the final point PCR analysis was performed for Dengue and Zika. Nevertheless, no identification of arbovirus was obtained with RT-PCR, but 2 Zika positives were detected with Sanger sequencing. In contrast, there were no officially reported cases of Zika in 2023. This demonstrates a possible risk of infection in the human populations who live in the Caja Fuego and San Gregorio communities. It is recommended that a vigilance campaign be implemented in this zone, in collaboration with the Ecuadorian Ministry of Public Health.